2017
DOI: 10.1103/physrevb.95.064429
|View full text |Cite
|
Sign up to set email alerts
|

Creation of unidirectional spin-wave emitters by utilizing interfacial Dzyaloshinskii-Moriya interaction

Abstract: International audienc

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
51
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 80 publications
0
51
1
Order By: Relevance
“…The spin-wave dispersions at 30 • become rather flat and therefore only a small group velocity v 0 g remains [37,42,43,50]. If the DMI-induced drift group velocity v DMI g ≈ v 0 g , the nonreciprocity is enhanced due to the interfacial DMI [37,51].…”
mentioning
confidence: 99%
“…The spin-wave dispersions at 30 • become rather flat and therefore only a small group velocity v 0 g remains [37,42,43,50]. If the DMI-induced drift group velocity v DMI g ≈ v 0 g , the nonreciprocity is enhanced due to the interfacial DMI [37,51].…”
mentioning
confidence: 99%
“…In the present work, we have demonstrated that, in addition to acting as self-cladding magnonic waveguides, conventional Bloch walls could behave just like this, provided one is capable of addressing individual walls in a dense array. Here, nonreciprocal propagation/emission of spin-waves does not require wave-vector selective excitation sources [30] and does not rely on the interfacial Dzyaloshinskii-Moriya interaction, the effect of which is sufficiently strong in ultrathin films only. It occurs as a consequence of a collective effect and of conventional dynamic dipolar interactions within the symmetry broken spin textures of Bloch walls, which have the advantage of being hosted by magnetic media with thickness in the tens of nanometer range, maybe better suited for future applications.…”
mentioning
confidence: 99%
“…In analogy to the case in Ref. [33], the presence of spin waves localized in the DMI strip can trigger a stimulated splitting, implying k 1 = k b in (16). We are also interested in the normal-incident case, so the wave vector of the three-magnon splitting can be determined as where k 2y ≈ k 2 i − 2k 2 b − C. This indicates that the three-magnon splitting processes can only happen when k i ≥ 2k 2 b + C, which requires the frequency of the incoming spin waves higher than a critical value…”
Section: Three-magnon Interactions Arising In a Magnetic Stripmentioning
confidence: 80%